Structural rehabilitation of a middle byzantine ruin and the masonry building constructed above the ruin. Part II: The building. (November 2019) - Gunes, Baris; Cosgun, Turgay; Sayin, Baris; Ceylan, Oguz
Abstract: The objective of this study, which consists of a pair of articles, is the structural rehabilitation of a vaulted ruin located on the historical peninsula of Istanbul, dated to the Middle Byzantine period, and a masonry building constructed at a later date on top of the structure. The first article, which constitutes the first part of the study, examined the seismic performances of the historical ruin considering the states; (i) before the construction of the masonry building, (ii) after the construction of the masonry building and (iii) after the strengthening of the masonry building. The present article, which constitutes the second part of the study, presents the seismic assessment of the masonry building's current state located on the historical ruin and a strengthening method proposed for the building in order to achieve its target seismic performance level. Fieldwork and numerical analyses were conducted to this end. The effectiveness of the proposed method is revealed by modal analysis, pushover analysis and kinematic limit analysis in order to determine the global & local failure mechanisms and the seismic performance levels of the current and strengthened states of the masonry building. The findings of the study are significant in terms demonstrating the interaction between historical ruins and buildings constructed above them, and in defining the necessary strengthening applications required to achieve seismic safety in such structures. In addition, by adopting a holistic approach to the structural analysis and strengthening proposal, it is expected to serve as an important tool for the preservation of ruins dated to the Middle Byzantine period.